1778
DOI: 10.5962/bhl.title.46949
|View full text |Cite
|
Sign up to set email alerts
|

Nicolai Josephi Jacquin Miscellanea austriaca ad botanicam, chemiam, et historiam naturalem spectantia, cum figuris partim coloratis. Vol. I-[II]

Abstract: Semina oblonga, ex ov^ata bafi fenfim attenuata, nuda, apice inilrufba pappo feiTili, plumoio. Receptaculum paleaceum , paleis linearilanceolatis , calycis longitudine, apicem veilus tkventibus & fubierratis. Odor plantae nuUus. IBERIS CE?EMFOllA, tah. i. Thlafpi montanum, lerrato Cepeas folio, flore purpurafcente umbellato. Barr. rar. pag. 33. num. 365. ic, 848. Thlafpi alpinum, folio rotundiore, carnofo, purpurafcente flore. Tourn. injL 212. Antequam defcriptionem elegantis hujus plantae dem, prjenotandum ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1957
1957
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Solanum aggregatum was described from material cultivated in Vienna (Jacquin 1791). We have found no original material, but Atropa solanacea is cited in the protologue making this name homotypic with it (and with Solanum guineense ).…”
Section: Synoptic Character Listmentioning
confidence: 99%
“…Solanum aggregatum was described from material cultivated in Vienna (Jacquin 1791). We have found no original material, but Atropa solanacea is cited in the protologue making this name homotypic with it (and with Solanum guineense ).…”
Section: Synoptic Character Listmentioning
confidence: 99%
“…They argued that the epithet sarcoides should be applied to a sexual morph. Pirobasidium was based on the same epithet that was ascribed to Jacquin (1781) . Groves & Wilson (1967) suggested that the rules of nomenclature needed to be changed and based on this philosophical position attributed the description of a new asexual “species” to Höhnel (1902) alone.…”
Section: Rationale For Recommendationsmentioning
confidence: 99%
“… Albuca caudata was described by Jacquin (1791) and later illustrated ( Jacquin 1795 ) ( Fig. 1 ) after plants collected in “Promontorio bonae Spei", which “Apud nos in caldariis floret Decembri & Januario".…”
Section: Resultsmentioning
confidence: 99%